Methodical recommendations for workshops. Topic: "Resource Allocation Optimization Problem". Academic discipline: "Computer Mathematics. Part 1" - Chernova, N. L. (National Technical University "Kharkiv Polytechnic Institute", 2024)
Methodical recommendations and tasks for self-study activity on the topic "Resource Allocation Optimization Problem" are presented. A list of recommended literature is provided.
Keywords: methodical recommendations; workshops; resoumrce allocation optimization problem; computer mathematics. Part 1